2015
DOI: 10.1038/ncomms8879
|View full text |Cite|
|
Sign up to set email alerts
|

GABA signalling modulates plant growth by directly regulating the activity of plant-specific anion transporters

Abstract: The non-protein amino acid, gamma-aminobutyric acid (GABA) rapidly accumulates in plant tissues in response to biotic and abiotic stress, and regulates plant growth. Until now it was not known whether GABA exerts its effects in plants through the regulation of carbon metabolism or via an unidentified signalling pathway. Here, we demonstrate that anion flux through plant aluminium-activated malate transporter (ALMT) proteins is activated by anions and negatively regulated by GABA. Site-directed mutagenesis of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
342
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(360 citation statements)
references
References 41 publications
15
342
1
2
Order By: Relevance
“…The efflux of anions depolarizes membranes and this leads to inhibition of K + uptake. The negative regulation of ALMT proteins by GABA has been reported recently (Ramesh et al 2015). In general, the low potassium content in shoots of gad1/2 mutant could be the combined effects of reduced potassium retrieval from the xylem, an efflux of potassium from roots Mekonnen 261 and reduced uptake from the soil.…”
Section: Gaba-depletionmentioning
confidence: 99%
“…The efflux of anions depolarizes membranes and this leads to inhibition of K + uptake. The negative regulation of ALMT proteins by GABA has been reported recently (Ramesh et al 2015). In general, the low potassium content in shoots of gad1/2 mutant could be the combined effects of reduced potassium retrieval from the xylem, an efflux of potassium from roots Mekonnen 261 and reduced uptake from the soil.…”
Section: Gaba-depletionmentioning
confidence: 99%
“…To date, the ALMT family has been shown to be central to physiological processes such as control of stomatal aperture [5,6] and anion homoeostasis [7]. Furthermore, increasing attention is being paid due to their potential role in economically valuable traits such as fruit flavour [8] and grain filling [9], and more recently they have been shown to be key mediators of GABA (γ-aminobutyric acid) signalling [10]. Identification of the molecular actors in these processes is already helping guide marker-assisted breeding [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the ALMTs have a low overall sequence similarity with the GABA A receptors in animal cells, ALMTs contain a conserved motif that is similar to the GABA binding site on GABA A receptors. This intriguing result suggests that ALMTs may perform many other functions in plants which are still to be discovered [80].…”
Section: The Structure-function Relationship Of Almt Proteinsmentioning
confidence: 92%
“…Recently Ramesh et al [80] showed that the transport activity of several ALMTs expressed in Xenopus oocytes is very sensitive to inhibition by gamma-aminobutyric acid (GABA) and muscimol, an agonist of GABA A receptor. Subsequent studies suggest that ALMT proteins may be GABA receptors in plants and underlay novel signalling pathways associated with stress responses.…”
Section: The Structure-function Relationship Of Almt Proteinsmentioning
confidence: 99%